Integrating Artificial Intelligence in Human Resource Management: A Systematic Literature Review - I Putu Putra Astawa; I Gede Aryana Mahayasa (Management and Applied Social Studies Review, 2024)
Purpose –This study aims to present a comprehensive literature review on the application of AI in key HR functions, such as recruitment, training, performance evaluation, and performance management. This literature review covers the period from 2020 to 2024 to reflect the latest developments in this field. Methodology – A systematic analysis of the literature presents important findings related to the benefits, challenges, and trends of integrating AI into HR practices. Research highlights how AI can improve efficiency in the recruitment process through deeper data analysis, identification of potential candidates, and prediction of corporate culture fits. Findings –AI can also be used to provide personalized training according to the individual needs of employees, as well as evaluate performance more objectively through real-time data analysis. Originality – The contribution of the research results carried out is to provide a better understanding of the role of AI in improving the effectiveness and efficiency of HR management, as well as highlighting future research directions in integrating these technologies more effectively and sustainably.